Data_Sheet_1_Application of the food-energy-water nexus to six seafood supply chains: hearing from wild and farmed seafood supply chain actors in the United States, Norway, and Vietnam.DOCX - Jillian P. Fry; Rachel E. Scroggins; Taryn M. Garlock; David C. Love; Frank Asche; Mark T. Brown; Elizabeth M. Nussbaumer; Ly Nguyen; Lekelia D. Jenkins; James Anderson; Roni A. Neff (2024)
Introduction The food-energy-water (FEW) nexus highlights the interdependencies between the systems that people rely on for these essential resources. For example, globally, over two thirds of freshwater withdrawals are used to produce food, and another 10% is used during energy generation. In addition, the food system uses one eighth of global net energy. Seafood is a nutritionally important food, and it is critical to use freshwater and energy resources efficiently throughout seafood supply chains to safeguard future supplies and to reduce environmental impacts. Diverse seafood production methods result in highly variable resource use across supply chains, which may contribute to siloed efforts within supply chains to improve efficiency, instead of larger efforts that involve multiple seafood supply chains. Additionally, efforts to develop and implement efficiency strategies must be informed by fishers, aquaculturists, processors, and other seafood supply chain actors to avoid investing time and resources into strategies that will have low uptake. A significant proportion of seafood is imported into the U.S., so engaging with industry and stakeholders in the U.S. and abroad is critical for understanding and improving the FEW nexus associated with seafood consumed by Americans. Methods To understand how resources are being used, current and potential strategies to improve resource use, and relevant motivations and barriers, we conducted 47 semi-structured interviews from 2019 to 2021 with seafood supply chain actors, including producers and processors. Seafood supply chains included were farmed catfish produced in the U.S., farmed pangasius and shrimp produced in Vietnam, farmed Atlantic salmon produced in Norway, and wild-caught sockeye and pink salmon caught in the U.S. Results We provide detailed descriptions of stages within each supply chain regarding resource use and efficiency strategies, and report higher-level findings that apply across supply chains. There was variation across settings regarding how ...